Teleconsultation Benefits for School Counselors: An Optional Path for Enhancing Educational Support System - Sinaga, M. Harwansyah Putra; Haryadi, Rudi; Nurodin, Nurodin; Warren, Jeffrey M. (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
Consultation is part of school counselor services. As a professional, counselors also need ongoing and continuous consultation with other professionals in order to overcome frustration, improve skills, self-development, and advocacy. One of its forms is teleconsultation. Teleconsultation is an option in order to improve the education support system. The purpose of this study was to describe the implementation of teleconsultation carried out by school counselors to other professionals (senior counselors). The teleconsultation in question is a consultation using the chat feature on the Whatsapp application. Data were collected by interviewing 2 school counselors as participants and then analyzed using the Miles and Hubermann techniques. The results of this study indicate that the reasons for effectiveness, efficiency, and professional experience of consultants are the reasons counselors use teleconsultation. School counselors gain new understanding and feel satisfied after teleconsultation is carried out. Not only that, they also apply the results of teleconsultation with consultants. Teleconsultation answers their needs as school counselors and will continue to use teleconsultation in the future. Thus, the professional activities of school counselors increase with the existence of teleconsultation so that it can be used as an option to improve the educational support system.